Atomic layer deposited zinc oxide thin film on pencil graphite for DNA sensor applications - Gungor, Mustafa Ali; Alev, Onur; Kaya, Hilmi Kaan; Arslan, Leyla Colakerol; Buyukkose, Serkan; Ozturk, Zafer Ziya; Kuralay, Filiz (Elsevier, 2023)
Atomic Layer Deposition (ALD) enables precise thin-film deposition on electrode substrates for electrochemical sensors. In this work, we present the first example of ALD grown zinc oxide (ZnO) deposition on pencil graphite surfaces for deoxyribonucleic acid (DNA) sensory applications, including its detection and DNA damage investigation. For DNA sensing studies, the use of highly productive materials is essential. In this context, the ZnO modified pencil graphite electrodes (ZnO/PGEs) exhibited good electrochemical properties that make them a suitable substrate. ZnO films were characterized using scanning electron microscopy (SEM), ultraviolet-visible (UV-Vis) spectroscopy, photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), and electrochemical methods. The DNA recognition capability of the thin film coated electrodes was tested by using differential pulse voltammetry (DPV), which showed a linear response ranging from 1 mg L-1 to 200 mg L-1 based on the oxidation of guanine (G) with a limit of detection value (LOD) of 0.53 mg L-1 (n = 3). In addition to this, impedimetric monitoring of oxidative DNA damage was performed in the presence of copper(II)/hydrogen peroxide (Cu(II)/H2O2) reagents, and protection studies were conducted in the presence of ascorbic acid. ZnO thin film-based electrodes exhibited good sensor performance in terms of sensitivity, stability, and reproducibility.
Keywords: Atomic layer deposition; DNA; Oxidative DNA damage